(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to instill the influence of leadership, work discipline, and work ethic on employee performance at the Regional Disaster Management Agency (BPBD) of North Sumatra Province. Data collection was conducted through a survey method using questionnaires distributed to employees, and supplemented by interviews and discussions with leaders and related staff. Data analysis was conducted through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of the study indicate that leadership, work discipline, and work ethic each have a positive and significant effect on employee performance partially. In addition, these three variables simultaneously also have a positive and significant effect on improving employee performance. These findings emphasize the importance of policy enforcement, discipline enforcement, and work ethic development in efforts to improve the performance of apparatus within the BPBD of North Sumatra Province.